Extraction of samarium, europium And gadolinium using [trialkylammonium][di-(2- Ethylhexyl) phosphate] - Nurul Ain, Ismail (2023)
The separation of the rare earth elements is a difficult task owing to the chemical similarity of the lanthanides. The conventional solvent extraction method using (di-(2-ethylhexyl) phosphoric acid), DEHPA requires a large number of stages and consumes significant amounts of acid and base for effective separation. In this study, a bifunctional ionic liquid [trialkylammonium][di-(2-ethylhexyl)phosphate], [A336][DEHPA] was investigated as an alternative extractant for the separation of samarium, europium and gadolinium was compared to DEHPA. The effect of acid type (acid nitric, HNO3, hydrochloric acid, HCl, sulfuric acid, H2SO4) and concentration (1.5M-5.0M) , as well as organic to aqueous (O:A) phase ratio (1:1,3:2,7:3,4:1,9:1) were studied using one-factorat- time (OFAT) experimental method. The response surface methodology (RSM) using historical data design (HDD) was further used to optimized and validate the results. The number of extraction and scrubbing stages were then calculated according to Counter Current Theory Model and were validated experimentally. Techno-economic analysis was performed for both extractants, with the published data on 2-ethylhexyl phosphoric acid mono 2-ethylhexyl ester (EHEHPA) serving as the baseline. The best condition for samarium separation was achieved using [A336][DEHPA] with separation factor of 2.93, in comparison with DEHPA with 1.93. The optimum samarium separation condition was using 3.0M HNO3 with O:A of 4:1 for [A336][DEHPA], and 2.0M HCl with O:A of 7:3 for DEHPA. The separation of remaining elements, europium and gadolinium, showed [A336][DEHPA] have better separation capabilities against DEHPA with separation factors of 3.44 and 2.38, respectively. The optimum condition for separation of europium and gadolinium was 3.5M HNO3 at O:A of 4:1 for [A336][DEHPA] and 3.0M. HCl at O:A of 4:1 for DEHPA. The total number of extraction and scrubbing stages for the entire process calculated and validated for each extractant was 30 stages for [A336][DEHPA] and 46 stages for DEHPA. The benchmark selected for techno-economic comparison in this study was EHEHPA, a well-established extractant used in industrial applications. The analysis revealed that the overall cost for [A336][DEHPA] was 46.49% lower than the cost of the baseline (EHEHPA), indicating a substantial reduction in expenses achieved by the new extractant. Additionally, DEHPA demonstrated a cost reduction of 34.15% compared to the baseline. This difference was primarily attributed to the higher cost associated with the development of the mixer settler for EHEHPA and DEHPA. In conclusion, [A336][DEHPA] demonstrated superior separation capabilities with higher separation factors, lower reagent consumption, and reduced costs compared to other extractants. It offers a greener alternative with a smaller number of stages required for rare earth processing. Therefore, [A336][DEHPA] holds great promise for industrial mineral processing in the future.